Clarifying the relationship between torpor and anthropogenic extinction risk in mammals. (1st April 2014) - Hanna, E.; Cardillo, M.
Abstract The ability to undertake torpor has been linked with human‐mediated extinction risk in mammals, but whether torpor serves to elevate or decrease extinction risk, and the mechanism by which it does so, remain controversial. We attempt to clarify the torpor – extinction risk association in a phylogenetic comparative analysis of 284 Australian mammal species. We show that the association is strongly mediated by body size. When body mass is included as a covariate, regression models show a negative association between the ability to undertake torpor and current threat status. This association is present in two categories of mammal species likely to be at particular risk from introduced predators (medium‐sized species and species listed as threatened by predation in the International Union for Conservation of Nature Red List), but there is no association among species not in these categories. This suggests that torpor reduces vulnerability to predators, perhaps by limiting the amount of time spent foraging. However, the association between torpor and extinction risk is also stronger in smaller species, which are more likely to benefit from a reduced energy budget in Australia's low‐productivity and unpredictable environment. We conclude that the ability to undertake torpor is clearly an advantage to mammal species in coping with human impacts, and that this advantage is conferred through a combination of reduced exposure to predators and reduced energy requirements.